Contemporary Opportunity for Prehabilitation as Part of an Enhanced Recovery after Surgery Pathway in Colorectal Surgery - Ven Fong, Zhi; Chang, David C.; Lillemoe, Keith D.; Nipp, Ryan D.; Tanabe, Kenneth K.; Qadan, Motaz (Clinics in Colon and Rectal Surgery, 2019)
The implementation of upfront, preoperative habilitation (“prehabilitation”), as opposed to postoperative habilitation (rehabilitation), provides a unique opportunity to optimize surgical outcomes, while ensuring that patients receive necessary conditioning that may otherwise be significantly delayed by postoperative complications. In this review, opportunities to design, implement, monitor, and evaluate a surgical prehabilitation program in colorectal surgery are discussed, and broken down to include emotional, physical, and nutritional aspects of care in the preoperative setting.
Keywords: prehabilitation; optimization; colorectal surgery; surgical oncology; cancer; nutrition; exercise